Correlación del sistema POSSUM vs APACHE-II en cirugía gastrointestinal programada y urgente. Riobamba, 2019 - Daniela Alejandra, Escobar Valverde (2020)
Predictive scales are not only a research method, but also a method to evaluate the performance of surgical units. The general purpose of this research was to correlate the predictive scales for risk of morbidity and mortality POSSUM and APACHE-II in patients undergoing scheduled and urgent gastrointestinal surgery at IESS Hospital, Riobamba during 2019. A descriptive, retrospective cross-sectional study was carried out with a series of cases. Using inclusion and exclusion techniques, the research sample was 201 patients. The POSSUM diagnostic scale had greater discriminatory power than the APACHE-II scale for variable mortality in urgent and scheduled gastrointestinal surgery, since the area under the curve (AUC) was greater; AUC for POSSUM = 0.938 (CI: 0.849-1.000), AUC for APACHE II = 0.911 (CI: 0.0.829-0.992). The POSSUM scale has a correlation coefficient value higher than APACHE-II (0.452 vs 0.137), and a higher coefficient of determination (0.2047 vs 0.0189). The largest number of patients who underwent surgery for emergency and scheduled gastrointestinal surgery comprised an age range of 50-54 years, representing 11.44%, in addition to 55.23% of patients undergoing surgery were male. Finally, it was determined that POSSUM scale has a better discriminatory capacity, so it can be used as a tool to predict the risk of morbidity and days of post-surgical hospital stay.